2015 Integrated Communication, Navigation and Surveillance Conference (ICNS) 2015
DOI: 10.1109/icnsurv.2015.7121246
|View full text |Cite
|
Sign up to set email alerts
|

4 Dimensional trajectory functionalities for air traffic management systems

Abstract: The research presented in this paper focuses on the conceptual design of an innovative Air Traffic Management (ATM) system featuring automated 4-Dimensional Trajectory (4DT) Planning, Negotiation and Validation (4-PNV) functionalities to enable Intent Based Operations (IBO). In order to meet the demanding requirements set by national and international organisations for the efficiency and environmental sustainability of air transport operations, a multi-objective 4DT optimization algorithm is introduced that re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 20 publications
0
32
0
Order By: Relevance
“…2. Gardi et al (2015a) explained the four-dimensional trajectory optimization algorithm that uses Matlab GPOPS for the multiple-phase optimal control problem (Rao et al 2010) and a smoothing algorithm (Gardi et al 2015b) similar to the 3D Dubin curves. Beyond the feasible criteria, their approach proposed to optimize the UAV trajectory with respect to the weather conditions, the required time of arrival, and the required initial and final trajectory headings.…”
Section: Power and Fuel Criteriamentioning
confidence: 99%
“…2. Gardi et al (2015a) explained the four-dimensional trajectory optimization algorithm that uses Matlab GPOPS for the multiple-phase optimal control problem (Rao et al 2010) and a smoothing algorithm (Gardi et al 2015b) similar to the 3D Dubin curves. Beyond the feasible criteria, their approach proposed to optimize the UAV trajectory with respect to the weather conditions, the required time of arrival, and the required initial and final trajectory headings.…”
Section: Power and Fuel Criteriamentioning
confidence: 99%
“…In the literature, the term modelling is characterised by considerable flexibility in meaning. For instance, in research in the ATC context alone, modelling may refer to automation (Rungta et al, ), simulation (Jafer, Chhaya, Durak, & Gerlach, ), software modelling (Qu, Wu, Yang, & Wang, ), traffic management (Gardi, Sabatini, Kistan, Lim, & Ramasamy, ), and/or cognition (Niessen, Eyferth, & Bierwagen, ). In this study, we adopted a service perspective.…”
Section: Research Backgroundmentioning
confidence: 99%
“…The research shown in this paper is a direct response to market demand, because the existing software used in eye tracking examinations performed today utilizing mobile eye trackers does not provide continuous analysis of AOI in the registered video streams. The demand for continuous AOI analysis is great [11][12][13][14][15][16]. The technology shown in the paper will be applied mainly in the industries of aeronautics, forwarding, goods haulage, transportation, and training; however, it is not limited to these alone.…”
Section: Introductionmentioning
confidence: 99%